Pengendalian Mutu Kompetensi Guru Melalui Program Supervisi Akademik : Supervisi Akademik - Agustina, Anna; Failasuf Fadli (IAIN Ambon, 2024)
Abstract: The aim of the academic supervision program is to improve the quality of teaching learning process as well as the teacher’s teaching competency. Improving the quality of teachers, both in professional and pedagogical competence, is surely provide huge benefit in improving the quality of learning. However, there are some problems found in the implementation of the teacher supervision program that make the supervision less optimal. The reason is the inconsistency of the implementation of this program. Moreover, this program seems to be implemented only for formality. This research aimed to determine the ongoing process of academic supervision at SMPIT Assalaam Boarding School (Assalaam Islamic Integrated Boarding School) Pekalongan. The research was carried out using a descriptive qualitative method, the required data was obtained through a process of interviews, discussions and documentation. The results of the research show that the academic supervision activities carried out at SMPIT Assalaam Boarding School Pekalongan have fulfilled the principles of supervision. Academic supervision is carried out to oversee the learning process as an institution's effort to provide quality assurance of education. Academic supervision is carried out through the following stages: the first is the socialization of the supervision program; the second is consultation on learning tools; the third is a class visit to the target teacher to be supervised; the fourth is a reflection on the implementation of teaching and learning activities; the fifth is scoring the results of academic supervision as a conclusion on the teacher's competency achievements; and then the preparation of follow-up activities of the supervision. Through academic supervision activities, school principals can provide guidance to teachers to improve the quality of learning